(3GdYbO GdefXe ddMcGe ajeG jLQi Hjf CjOjge ef GdYbhO hGdCMcGes - (3CHh GdbGSe Sdehf Hf Ydj Hf Sdehf GdcfGfj,J (B767 (3g` s ((3EHQGgje Hf ehSi GdMSfGhi s)
(3ChdgG (B:s
(3dGjdRe EPG de jbY PcQ Ydi eYjf hgj QhGjI GHf GdbGSe Yf eGdc hGdKGfi Efg dGRe hgj QhGjg eWQa s
(3BNQgG (B:s
(3hbGd GHf QTO ai GdJYbH EfeG JLH Ydjg GdYbhHI hgGgfG GfJgi Gdbhd HfG ai gPG GdeLehY hGdMeO ddg ced hGdMeO ddg Mb MeOg hGdUdGI Ydi SjOfG eMeO fHjg GdeUWai hYHO Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B114 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B643s
Keywords: (3Gdabg GdeGdcjs